2020
DOI: 10.3389/fimmu.2020.01918
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Roles and Mechanisms of Immune Cell Death in Sepsis

Abstract: Sepsis was first described by the ancient Greek physicians over 2000 years ago. The pathophysiology of the disease, however, is still not fully understood and hence the mortality rate is still unacceptably high due to lack of specific therapies. In the last decade, great progress has been made by shifting the focus of research from systemic inflammatory response syndrome (SIRS) to multiple organ dysfunction syndrome (MODS). Sepsis has been re-defined as infection-induced MODS in 2016. How infection leads to MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 160 publications
0
60
0
1
Order By: Relevance
“…At present, the uncontrolled inflammatory response is considered to be the basis for the pathogenesis of sepsis. The release of inflammatory factors in the early stage of sepsis leads to amplification of an inflammatory cascade and tissue and organ damage (20)(21)(22)(23). TNF-α and IL-6 are associated with occurrence and progress of inflammatory reactions in sepsis (24).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the uncontrolled inflammatory response is considered to be the basis for the pathogenesis of sepsis. The release of inflammatory factors in the early stage of sepsis leads to amplification of an inflammatory cascade and tissue and organ damage (20)(21)(22)(23). TNF-α and IL-6 are associated with occurrence and progress of inflammatory reactions in sepsis (24).…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal injection of HMGB1 did not show such effect [45]. Regarding the inflammatory reaction, HMGB1 mediates endotoxin shock [46], and can cause multiple organ dysfunction syndrome (MODS) [47]. It is "a late mediator of sepsis" with postponed release in comparison with "early mediators of sepsis" represented, e.g., by TNF-α [48].…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing use of antibiotics and various anti-in ammatory factors in recent years, most patients will survive the systemic acute in ammatory reaction period, but subsequently enter a longer-lasting immune dysfunction state [22]. Studies have found that the key cause of immune dysfunction in patients with sepsis is the death of lymphocytes, especially T and B lymphocyte apoptosis, is a major factor in immune dysfunction [23]. CD4+ can help B lymphocytes produce antibodies and induce T lymphocytes to transform into effector cells, and is a surface marker of Ti/Th.…”
Section: Discussionmentioning
confidence: 99%